Efektivitas Model Pembelajaran Membaca Permulaan Pass Terhadap Kemampuan Membaca Nyaring Siswa Kelas II SD - R.R Zakiyah Munawaroh; Muhardila Fauziah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This research examines the impact of the Planning, Attention, Simultaneous, and Successive Processing (PASS) instructional model on second-grade students' reading aloud performance. This research utilized a quantitative approach with a pre-experimental design employing a One Group Pretest-Posttest framework. The participants consisted of second-grade students at SD Muhammadiyah Ambarbinangun. Data were gathered through pretest and posttest instruments specifically designed to assess students' initial reading abilities and reading aloud proficiency. Analysis of the data was conducted through descriptive statistics, normality tests, N-Gain calculations, and hypothesis testing. The findings revealed a significant enhancement in students' reading aloud skills following the implementation of the PASS model. The mean posttest score exceeded the pretest score, and the N-Gain results demonstrated a moderate to high improvement category. Through hypothesis testing, it was confirmed that the PASS learning model effectively enhanced students' reading aloud skills. Consequently, the PASS model can be recommended as an alternative instructional strategy to develop early reading and reading aloud skills among lower-elementary grade students.